Correction: Income inequality and its relationship with loneliness prevalence: A cross-sectional study among older adults in the US and 16 European countries. - Thamara Tapia-Muñoz; Ursula M Staudinger; Kasim Allel; Andrew Steptoe; Claudia Miranda-Castillo; José T Medina; Esteban Calvo (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274518.].